2013
DOI: 10.1007/s11099-013-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Responses of photosynthetic characteristics and antioxidative metabolism in winter wheat to post-anthesis shading

Abstract: In a field experiment, two winter wheat (Triticum aestivum L.) cultivars, Tainong 18 (a large-spike cultivar) and Jinan 17 (a multiple-spike cultivar), were treated with 78% (S1), 50% (S2), and 10% (S3) of full sunshine (S0, control) from anthesis to maturity to determine the responses of photosynthetic characteristics and antioxidative enzyme activities in a flag leaf. Compared with S0 treatment, the chlorophyll (Chl) content and maximal efficiency of photosystem II (PSII) photochemistry (F v /F m ) of flag l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Despite the reduction of the leaf N content, chlorophyll content (SPAD values) increased with shade in accordance with other shading studies on cereal crops (Li et al., 2010; Wang et al., 2015; Xu et al., 2013; Zheng et al., 2011). Shade‐adapted species typically have high leaf chlorophyll content compared with light plants, a trait that maximizes light capture (Valladares & Niinemets, 2008; Zhen & van Iersel, 2017) and commonly acclimation to shade results on greater leaf chlorophyll/Nitrogen ratio (Evans, 1996).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the reduction of the leaf N content, chlorophyll content (SPAD values) increased with shade in accordance with other shading studies on cereal crops (Li et al., 2010; Wang et al., 2015; Xu et al., 2013; Zheng et al., 2011). Shade‐adapted species typically have high leaf chlorophyll content compared with light plants, a trait that maximizes light capture (Valladares & Niinemets, 2008; Zhen & van Iersel, 2017) and commonly acclimation to shade results on greater leaf chlorophyll/Nitrogen ratio (Evans, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…Xu et al. (2013) reported lower values of soluble sugars during the whole grain‐filling phase in the flag leaves of shaded plants (50% and 90% of shading) with respect to full‐sunlight plants in two wheat cultivars. However, low‐intensity shading plants (22% of shading) tended to accumulate more soluble sugar than control plants, especially in shade‐tolerant cultivars (Xu et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…NS, no shading treatment; SE, shading from the 1st day to the 10th days after anthesis (shading at early filling stage for 10 days, SE); Five potassium rate, 0 (K0), 50 (K50), 100 (K100), 150 anthesis demonstrated an important link with the formation of spike grain number (Ferrante et al, 2010). Previous studies showed that the major reason for shading decreasing grain yield as reflected in the reduced TKW was due to depressed plant nitrogen accumulation, leaf photosynthetic rate and grain filling rate (Jia et al, 2011;Xu et al, 2013;Li et al, 2017). The reduction of grain weight had most serious impact on wheat yield (Mu et al, 2010), which was dependent on the number and size of endosperm cells.…”
Section: Figure 4 |mentioning
confidence: 99%
“…The results demonstrated that shading reduced the nitrogen content of plant leaves (Pons and Pearcy, 1994) and the solar energy use efficiency of winter wheat leaf through depression of chlorophyll a/b and non photochemical quenching coefficient (NPQ) (Li et al, 2010). Moreover, the wheat leaf photosynthetic rate was also reduced by depressing the leaf temperature, stomatal conductance and transpiration rate under shading stress (Xu et al, 2013;Dong et al, 2019). Shading stress also resulted in changes to plant carbohydrate accumulation and distribution, causing carbon metabolism imbalance, and eventually led to yield reduction (Grashoff and d'Antuono, 1997;Mu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies to date have used shading to investigate the effects of low intensity light on crop growth and development (Xu et al, 2013;Cui et al, 2015). Many studies have shown that shade treatment not only reduces the intensity of light but also increases the diffuse light proportion (Gu et al, 2002;Greenwald et al, 2006) and changes the light spectral quality (Bell et al, 2000).…”
Section: Introductionmentioning
confidence: 99%